OC-024 Prolonged Platelet Activation in Patients with Acute Upper Gastrointestinal Bleeding. (4th June 2013) - Disney, B R; Watson, R; Blann, A; Lip, G; Tselepis, C; Anderson, M
Abstract : Introduction: Acute upper gastrointestinal bleeding (AUGIB) is a common reason for hospital admission and is associated with significant cardiovascular (CVS) morbidity and mortality. Patients who have aspirin withheld for 8 weeks following AUGIB have significantly higher rates of CVS events. 1 We previously demonstrated that patients with AUGIB have significantly higher levels of platelet activation during the index hospital admission. 2 This study aimed to assess the level of platelet activation and reactivity 12 weeks following admission for AUGIB. Methods: Patients admitted to SWBH NHS Trust with AUGIB were recruited. Dyspeptic patients attending for diagnostic OGD were used as controls. To assess platelet activation citrated whole blood was incubated at room temperature with monoclonal mouse antibodies against constitutively expressed platelet marker CD42a-PerCP, and markers of platelet activation PAC1-FITC, and CD62P-APC. Incubation was terminated after 15 minutes. Samples were analysed using a FACSCalibur flow cytometer. Platelets were identified on the basis of their forward and side scatter properties and the presence of the CD42a platelet-specific marker. CD62P and PAC1 expression were measured by the percentage of platelets expressing these markers. Data are expressed as mean±SD for normally distributed parameters and median (interquartile range) for non-normally distributed parameters. Statistical analysis was performed using SPSS 18.0 software. Results: A total of 24 patients with AUGIB and 18 controls were recruited. Patients were age and gender matched. The mean age of the AUGIB group is 66.4 ± 18.2 years, and the control group 62.8 ± 6.1years. Significant differences were seen in all markers of platelet activation (table 1). Conclusion: Patients presenting with AUGIB have prolonged levels of platelet activation for at least 12 weeks following the index event. This phenomenon may be further prolonged and further studies are required. This may explain the excess of CVS events in AUGIB patients. In patients with high cardiovascular risk early re-introduction of aspirin should be considered. Disclosure of Interest: None Declared References: Sung JJ, Lau JY, Ching JY, Wu JC, Lee YT, Chiu PW, Leung VK, Wong VW, Chan FK. Continuation of low-dose aspirin therapy in peptic ulcer bleeding: a randomised trial. Ann Intern Med. 2010 Jan 5; 152(1):1–9. Disney BR, Watson R, Blann A, Lip G, Tselepis C, Anderson M. Platelet activation in acute upper gastrointestinal bleeding. Gut 2012; 61 (Suppl 2): A361.